Pore structural evolution of shale following thermochemical treatment. (February 2020) - Rigby, Sean P.; Jahan, Hosne; Stevens, Lee; Uguna, Clement; Snape, Colin; Macnaughton, Bill; Large, David J.; Fletcher, Robin S.
Abstract: Shales experience heat treatment concurrent with the presence of water or steam during reservoir engineering interventions, such as high pressure water fracking and in-situ combustion of hydrocarbons. This work utilises a novel technique, which is a combination of gas sorption overcondensation and integrated mercury porosimetry experiments, not used before for any type of porous material, to study the pore structure of a shale rock, and its evolution following thermal treatment in the presence of water. Overcondensation allows the extension of gas sorption beyond the limits of conventional experiments to enable direct study of macroporosity. Scanning curve experiments, initiated from the complete boundary desorption isotherm, that can only be obtained for macropores by overcondensation experiments, has revealed details of the relative pore size spatial disposition within the network. In particular, it has been found that the new large voids formed by treatment are shielded by relatively much narrower pore windows. Use of a range of different adsorbates, with differing polarity, has allowed the chemical nature of the pore surface before and after treatment to be probed. Integrated rate of gas sorption and mercury porosimetry experiments have determined the level of the particular contribution to mass transport rates of the newly introduced porosity generated by thermal treatment. Combined CXT and mercury porosimetry have allowed the mapping of the macroscopic spatial distribution of even the new mesoporosity, and revealed the degree of pervasiveness of the new voids that leads to a thousand-fold increase in mass transport on thermal treatment. Highlights: Overcondensation method allows application of nitrogen sorption to macroporous rocks. Detailed morphology of pore network obtained from sorption scanning curves. Integrated rate of gas sorption and mercury porosimetry allows direct assessment of contribution of particular pores to mass transport. Thermochemical treatment created completely new pore network that raised mass transport rate by factor of ~1000.